リツキシマブ導入療法とその後の酢酸グラチラマー療法 (2016)
本発明は、ある形態の多発性硬化症に罹患する、またはクリニカリーアイソレーテッドシンドロームを呈する対象を治療する方法であって、対象へのある量の抗ＣＤ２０抗体の少なくとも２回の定期的な投与、その後の、対象へのある量の酢酸グラチラマーの定期的な投与を含み、量が、対象を治療するのに有効である方法を提供する。【選択図】 なし The present invention provides a method of treating a subject afflicted with a form of multiple sclerosis or presenting a clinically isolated syndrome comprising periodic administration of an amount of rituximab at least twice to the subject followed by periodic administration of an amount of glatiramer acetate to the subject, wherein the amounts are effective to treat the subject. The present invention also provides a method of treating a subject afflicted with an immune disease, comprising periodic administration of an amount of rituximab at least twice to the subject followed by periodic administration of an amount of glatiramer acetate to the subject wherein the amounts are effective to treat the subject, and wherein the immune disease is an autoimmune disease, an arthritic condition, a demyelinating disease, an inflammatory disease, multiple sclerosis, relapsing-remitting multiple sclerosis, diabetes mellitus, psoriasis, rheumatoid arthritis, inflammatory bowel disease, Crohn's disease, or systemic lupus erythematosus.